2010
DOI: 10.1038/ejcn.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Fat intake and asthma in Spanish schoolchildren

Abstract: Objectives: To study the relationship between lipid, fatty acid and lipid-rich food intake and current asthma in a group of Spanish schoolchildren. Subjects/Methods: The subjects of this cross-sectional study were 638 Spanish schoolchildren (8-13 years of age). The weight and height of all the subjects were recorded. A questionnaire, completed by the subjects' parents, was used to obtain personal and health information. Current asthma was established when the children had ever had asthma, if they had been diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
(46 reference statements)
1
45
1
1
Order By: Relevance
“…Sugar consumption during the perinatal period was associated with severe asthma symptoms in 6-and 7-yr-old children [28]. An increased intake of saturated fatty acids was also found to be related to the risk of asthma in children [29].…”
Section: Discussionmentioning
confidence: 83%
“…Sugar consumption during the perinatal period was associated with severe asthma symptoms in 6-and 7-yr-old children [28]. An increased intake of saturated fatty acids was also found to be related to the risk of asthma in children [29].…”
Section: Discussionmentioning
confidence: 83%
“…29,34 Lower levels of n-3 fatty acids have been found in asthmatics relative to control subjects, 35 but others found no association between levels of n-3 fatty acids and asthma in schoolchildren aged 8 to 13 years. 36 In addition, the optimal intake of n-3 fatty acids in young children remains controversial. In 2002, the US Institute of Medicine concluded that there is insufficient evidence to provide clear recommendation on n-3 PUFA intake in children, 37 100 mg per day can improve visual function but evidence does not permit to define an age specific dietary recommendation for EPA and DHA from 2 years onward.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, fast-food consumption was associated Dietary factors, body weight, and screen time in US children with and without asthma 5 with asthma for Mexican children ages 6-8 and 11-14 years from several randomly chosen elementary schools (Gutiérrez-Delgado et al, 2009). The risk of asthma was more likely with increased intakes of saturated fatty acids, palmitic acid and butter in a cohort of Spanish elementary school children (Rodríguez-Rodríguez et al, 2010). The researchers concluded that the risk of current asthma in the children was elevated with increased intakes of saturated fatty acids, palmitic acid and butter.…”
mentioning
confidence: 88%